Adaptive fuzzy tracking control for a class of high-order switched uncertain nonlinear systems. Issue 15 (October 2017) - Wang, Xinyong; Li, Hongmin; Zong, Guangdeng; Zhao, Xudong
Abstract: In this paper, adaptive fuzzy tracking control is investigated for a class of high-order switched nonlinear systems. The considered systems possess the characteristic of completely unknown nonlinear functions and arbitrary switchings. An efficient fuzzy adaptive control method is established by combining the common Lyapunov function method with adding a power integrator approach. A common assumption that is widely used in high-order nonlinear systems with or without switching is removed. Because the unknown nonlinearities can be approximated by using fuzzy logic systems, our proposed method is more flexible and applicable. Furthermore, some effective parameters are introduced such that the obtained results can guarantee that the practical output tracking performance can be realized via easily tuning the controller design parameters. On the other hand, to solve the problem of over-parameterization, a result with only one adaptive law is given. Finally, simulation results are addressed to show the effectiveness of the theoretical approaches.